(untitled) (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
Reading skill is one of the foreign skills that must be mastered by students. The purpose of this research is to discover the problems faced by students of Ruhul Islam Anak Bangsa in studying Qira’ah. The data collection techniques used by researchers in this study were interviews and questionnaires. The data analysis techniques in this study are data collection, data reduction, data presentation, and conclusion drawing. And the results of this study are that there are two aspects of problems experienced by students in learning Qira’ah, namely: 1. Language aspects include the knowledge of the letters Arabiya, pronunciation, knowledge of Arabic Qawaid, and their lack of mastery of vocabulary. 2. Non-language elements include Islamic boarding school environmental factors, teachers, students, learning methods, learning media, motivation. The solutions provided by the teacher in learning Qira’ah are: The teacher explains the differences and the use between letters of the alphabet and hijaiyyah, the teacher reads the material beforehand and explains the language rules with famous examples, the teacher gives a general vocabulary which is often used in learning to be memorized after the lesson, provide motivation, use a variety of learning methods and media.